Differentiated Learning Strategies to Improve Science Literacy in Elementary Schools - Laily, Septika; Rahmi, Rina; Ikhwan, Muhamad Nur (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2024)
The aim of the research is to describe differentiated learning strategies to improve scientific literacy in elementary schools. The research method used is qualitative with a literature review approach . The object of this research is differentiated learning strategies and scientific literacy. Data is collected through documents or information searched on Google Scholar such as books, journals, articles and related documents. Data analysis used the Preferred Reporting Items for Systematic Review and MetaAnalysis (PRISMA) method. The results of the research are that differentiated learning can improve students' scientific literacy, especially in terms of understanding concepts and critical thinking skills. However, implementing this strategy faces several challenges, such as time constraints, the need for adequate resources, and adapting to diverse student needs. However, with the right support and careful planning, differentiated learning has great potential to improve the quality of science education. Differentiated learning can be applied at the early childhood education levels, elementary school, middle school, up to high school, where from the research that has been conducted in the 2017-2023 period, no one has used differentiated learning to increase scientific literacy, so further research is needed to discuss strategies, models or differentiated learning. towards scientific literacy. Previous research has used reading literacy but has not used scientific literacy, especially at the elementary school (SD) level. This research contributes to the educational literature by offering practical insights into the application of differentiated learning and its implications for students' scientific literacy.